Improvement in Nasal Obstruction and Quality of Life after Nasal Septoplasty with Turbinoplasty: A Pre- and Post-study - María A. García-Chabur; Juliana Castellanos; Gloria Corredor-Rojas; Mariana Salgar; Sergio Moreno; Martín Pinzón; Augusto Peñaranda (International Archives of Otorhinolaryngology, 2023)
Introduction Septoplasty and turbinoplasty are common surgical interventions used to relieve nasal obstructive symptoms. Since it is difficult to measure the degree of nasal blockage, current literature wonders about the frequent performance of these procedures. Objective To evaluate the perceived change in the nasal obstruction and the quality of life (QoL) of patients that underwent a septoplasty along with a turbinoplasty by applying subjective scales, to describe the correlation between those scales, and to study the impact of clinical factors in the postoperative outcomes. Methods Prospective observational study. The Nasal Obstruction Symptom Evaluation (NOSE), the Visual Analog Scale (VAS), and the Glasgow Benefit Inventory (GBI) were assessed. The paired sample Wilcoxon test was used to evaluate the difference between the pre- and postoperative surveys. The correlation coefficient between the subjective scales was calculated. A quantile regression was performed to evaluate the effect of surgery on the results adjusted for clinical and demographic variables. Results A total of 115 patients were interviewed. Postoperative NOSE scores were 45 points lower (95% confidence interval [CI]: - 53.53–- 35.46; p < 0.001) in comparison with the NOSE preoperative scores. Obesity was the only statistically significant factor associated with worse outcomes. Additionally, we found a high correlation between the NOSE and VAS scores and a negative correlation between the GBI and postoperative VAS scores. Conclusion Nasal septoplasty, when paired with a turbinoplasty, decreases nasal obstruction and improves QoL. Obesity was associated with worse results. There was a strong correlation between the NOSE and the VAS results and between the GBI and postoperative VAS results.